Malleable Curie Temperatures of Natural Titanomagnetites: Occurrences, Modes, and Mechanisms - (:unkn) unknown (My University, 2018)
Abstract Intermediate-composition titanomagnetites have Curie temperatures (Tc) that depend not only on composition but also on thermal history, with increases of 100°C or more in Tc produced by moderate-temperature (300–400°C) annealing in the laboratory or in slow natural cooling and comparable decreases produced by more rapid cooling (“quenching”) from higher temperatures. New samples spanning a range of titanomagnetite compositions exhibit reversible changes in Tc comparable to those previously documented for pyroclastic samples from Mt. St. Helens and Novarupta. Additional high- and low-temperature measurements help to shed light on the nanoscale mechanisms responsible for the observed changes in Tc. High-T hysteresis measurements exhibit a peak in high-field slope khf(T) at the Curie temperature, and the peak magnitude decreases as Tc increases with annealing. Sharp changes in low-T magnetic behavior are also strongly affected by prior annealing or quenching, suggesting that these treatments affect the intrasite cation distributions. We have examined the effects of oxidation state and nonstoichiometry on the magnitude of Tc changes produced by quenching/annealing in different atmospheres. Treatments in air generally cause large changes (ΔTc > 100°). In an inert atmosphere, the changes are similar in many samples but strongly diminished in others. When the samples are embedded in a reducing material, ΔTc becomes insignificant. These results strongly suggest that cation vacancies play an essential role in the cation rearrangements responsible for the observed changes in Tc. Some form of octahedral-site chemical clustering or short-range ordering appears to be the best way to explain the large observed changes in Tc.